Combination of Flow-Mediated Vasodilation and Nitroglycerine-Induced Vasodilation Is More Effective for Prediction of Cardiovascular Events. Issue 5 (May 2016) - Kajikawa, Masato; Maruhashi, Tatsuya; Hida, Eisuke; Iwamoto, Yumiko; Matsumoto, Takeshi; Iwamoto, Akimichi; Oda, Nozomu; Kishimoto, Shinji; Matsui, Shogo; Hidaka, Takayuki; Kihara, Yasuki; Chayama, Kazuaki; et al.
Abstract : Measurement of nitroglycerine-induced vasodilation has been performed to differentiate endothelium-dependent vasodilation from endothelium-independent vasodilation as a control test for flow-mediated vasodilation (FMD). Recently, nitroglycerine-induced vasodilation per se has been reported to be a useful marker of the grade of atherosclerosis. The present study aimed to evaluate the prognostic value of FMD combined with nitroglycerine-induced vasodilation for future cardiovascular events. We measured FMD and nitroglycerine-induced vasodilation in 402 subjects, including patients with cardiovascular diseases. During a median follow-up period of 32.3 months, 38 first major cardiovascular events (death from cardiovascular causes, acute myocardial infarction, stroke, and coronary revascularization) occurred. Receiver-operator characteristic curve analysis revealed that FMD alone and nitroglycerine-induced vasodilation alone can predict cardiovascular events with areas under the curve of 0.671 (cutoff 3.3%) and 0.692 (cutoff 11.6%), respectively. FMD combined with nitroglycerine-induced vasodilation predicts cardiovascular events with an area under the curve of 0.701. After adjustment for age, sex, and cardiovascular risk factors, above cutoff FMD (≥3.3%) and below cutoff nitroglycerine-induced vasodilation (<11.6%; hazard ratio, 5.55; 95% confidence interval, 1.61–25.46; P =0.006) and below cutoff FMD (<3.3%) and below cutoff nitroglycerine-induced vasodilation (<11.6%; hazard ratio, 7.20; 95% confidence interval, 2.37–31.36; P <0.001) remained strong independent indicator of cardiovascular events. These findings suggest that the combination of FMD and nitroglycerine-induced vasodilation measurements can more accurately predict cardiovascular events compared with FMD alone. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: UMIN000001167. Abstract : Supplemental Digital Content is available in the text.